High-elasticity grouting material and preparation method thereof

By preparing a high elastic grouting material, the problem of lack of elasticity and flexibility in structural displacement, vibration or temperature changes of traditional grouting materials is solved, and the high cost-effectiveness of the material, simplicity of construction, excellent weather resistance and wear resistance are achieved. .

CN119431646APending Publication Date: 2025-02-14SICHUAN TONGSHEN WATERPROOF ENG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411571628.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional grouting materials lack sufficient elasticity and flexibility when facing structural displacement, vibration or temperature changes, which easily create cracks, resulting in poor grouting effect and even failure.

Method used

Using a high elastic grouting material preparation method, by mixing the acrylate mixture with triethanolamine and other components, and adding compounds such as methyl methacrylate, styrene, vinyl trichlorosilane, and then adding initiators and fillers. Such as heavy calcium carbonate, alumina and nanosilicon dioxide, grouting materials with high elasticity and excellent weather resistance are obtained after stirring and curing.

Benefits of technology

This high elastic grouting material is low in cost, easy to construct, has excellent elasticity and flexibility, can adapt to minor deformation of the structure, extend the service life of the structure, and perform excellently in weather resistance, chemical resistance and wear resistance, ensuring that The durability of grouting effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005120600220000081
    Figure BDA0005120600220000081
  • Figure BDA0005120600220000091
    Figure BDA0005120600220000091
Patent Text Reader

Abstract

The invention relates to the technical field of new materials, and discloses a high-elasticity grouting material and a preparation method thereof.The method comprises the steps that after an acrylate mixture and triethanolamine are stirred to be evenly mixed, methyl methacrylate, styrene, vinyl trichlorosilane and N-hydroxymethyl acrylamide are sequentially added for stirring; adding an initiator and continuously stirring to promote the polymerization reaction; gradually adding heavy calcium carbonate, aluminum oxide and nano silicon dioxide, ensuring uniform distribution of the filler, adding butyl acrylate and hydroquinone, adding a defoaming agent and a dispersing agent, and continuously stirring to remove bubbles and ensure uniform distribution of the filler, so as to obtain a mixture; and pouring the mixture into a mold for curing to obtain the high-elasticity grouting material. The high-elasticity grouting material disclosed by the invention has excellent mechanical properties and durability, and is suitable for crack repair, water prevention, sealing and the like of various constructional engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a high-elastic grouting material and a preparation method thereof. Background Art

[0002] In modern construction projects, grouting materials are widely used in crack repair, structural reinforcement, waterproofing, foundation grouting and other fields. Although traditional grouting materials such as cement-based grouting materials have certain strength and stability, they often lack sufficient elasticity and flexibility in the face of structural displacement, vibration or temperature changes, and are prone to cracks, resulting in poor grouting effects or even failure. Therefore, it is particularly important to develop a grouting material with high elasticity.

[0003] Highly elastic grouting materials can adapt to small deformations of structures and reduce stress concentration caused by temperature changes, vibrations or load changes, thereby extending the service life of structures. At present, there are some highly elastic grouting materials on the market, such as polyurethane grouting materials and silicone grouting materials, but these materials are often expensive and have strict requirements on the construction environment and construction technology, which limits their wide application. Summary of the invention

[0004] In view of this, the present invention proposes a high elastic grouting material and a preparation method thereof, aiming to provide a high elastic grouting material with relatively low cost, simple construction and stronger adaptability. The material not only has excellent elasticity and flexibility, but also performs well in weather resistance, chemical resistance and wear resistance, and can effectively solve the problems encountered by traditional grouting materials in practical applications.

[0005] The present invention provides a method for preparing a high-elastic grouting material, comprising:

[0006] After the acrylate mixture and triethanolamine are stirred until uniformly mixed, methyl methacrylate, styrene, vinyl trichlorosilane and N-hydroxymethyl acrylamide are added in sequence and stirred;

[0007] Add initiator and continue stirring to promote the polymerization reaction;

[0008] Gradually add heavy calcium carbonate, alumina and nano-silica, and after ensuring that the fillers are evenly distributed, add butyl acrylate and hydroquinone, add defoamer and dispersant, continue stirring to remove bubbles and ensure that the fillers are evenly distributed, and obtain a mixture;

[0009] The mixture is poured into a mold and solidified to obtain the high elastic grouting material.

[0010] Preferably, after the acrylate mixture and triethanolamine are stirred until uniformly mixed, methyl methacrylate, styrene, vinyl trichlorosilane and N-hydroxymethyl acrylamide are added in sequence and stirred, the temperature is controlled to be 60±5°C.

[0011] Preferably, the initiator is potassium sulfate.

[0012] Preferably, the defoaming agent is a polyether defoaming agent.

[0013] Preferably, the dispersant is a polycarboxylic acid dispersant.

[0014] Preferably, the weight ratio of the acrylate mixture, triethanolamine, potassium persulfate, methyl methacrylate, styrene, vinyl trichlorosilane, heavy calcium carbonate, alumina, nano-silica, N-hydroxymethyl acrylamide, butyl acrylate, hydroquinone, diethylenetriamine, defoamer and dispersant is 15-22: 0.2-0.35: 0.25-0.3: 0.5-0.6: 0.25-0.3: 0.3: 1-2: 0.5-0.6: 0.2-0.3: 0.3: 0.3-0.4: 0.1: 0.15-0.2: 0.2: 0.2.

[0015] The present invention also provides a high-elastic grouting material, and the high-elastic grouting material is prepared by the preparation method of the high-elastic grouting material.

[0016] The invention also proposes an application of the high-elastic grouting material in preparing building materials.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The high-elastic grouting material of the present invention has a relatively low cost, which reduces the engineering cost and makes the material more economically competitive; the preparation method is simple and easy to operate, does not require complicated equipment and high technical requirements, and is convenient for application in various construction environments; the material has excellent elasticity and flexibility, can adapt to slight deformations of the structure, and reduce stress concentration caused by temperature changes, vibrations or load changes, thereby extending the service life of the structure; it has excellent performance in weather resistance, chemical resistance and wear resistance, can effectively resist the influence of harsh environment on material properties, and ensure the durability of the grouting effect; through the optimized formula and preparation process, the high-elastic grouting material of the present invention has better construction performance and curing performance, ensuring the smooth progress of the grouting operation and the final engineering quality.

[0019] In summary, the high elastic grouting material and preparation method thereof of the present invention not only solve the limitations of traditional grouting materials, but also have significant advantages in terms of cost, construction convenience, material performance, etc., and have broad application prospects. DETAILED DESCRIPTION

[0020] The exemplary embodiments of the present disclosure will be described in more detail below. Although the exemplary embodiments of the present disclosure are shown below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0021] Example 1 Preparation of high elastic grouting material

[0022] 1. Material composition

[0023] 1. Acrylate mixture - milky white liquid, 20 kg;

[0024] 2. Triethanolamine - analytical grade, 0.3 kg;

[0025] 3. Potassium persulfate - powder, 0.3 kg;

[0026] 4. Methyl methacrylate-industrial grade, content greater than 99%, 0.5 kg;

[0027] 5. Styrene-industrial grade, content greater than 99%, 0.3 kg;

[0028] 6. Vinyltrichlorosilane-industrial grade, content greater than 98%, 0.3 kg;

[0029] 7. Heavy calcium carbonate-paint grade, 800 mesh, 1 kg;

[0030] 8. Aluminum oxide - used to increase wear resistance, 0.5 kg;

[0031] 9. Nano-silicon dioxide - used to improve fluidity and crack resistance, 0.2 kg;

[0032] 10. N-hydroxymethyl acrylamide - industrial grade, content greater than 42%, 0.3 kg, used to increase curing strength;

[0033] 11. Butyl acrylate - technical grade, content greater than 98%, 0.4 kg, used to improve elasticity;

[0034] 12. Hydroquinone-industrial grade, content greater than 98%, 0.1 kg, used to improve antioxidant properties;

[0035] 13. Diethylenetriamine-industrial grade, content greater than 98%, 0.2 kg, used to promote cross-linking reaction;

[0036] 14. Defoamer - polyether modified siloxane defoamer, 0.2 kg, used to eliminate bubbles;

[0037] 15. Dispersant - Polycarboxylate sodium salt dispersant, 0.2 kg, used to improve filler dispersion.

[0038] 2. Preparation method

[0039] 1. Mixed reaction

[0040] Add the acrylate mixture (20 kg) and triethanolamine (0.3 kg) to the reaction kettle and stir until homogeneous.

[0041] 2. Cross-linking promotion

[0042] Methyl methacrylate (0.5 kg), styrene (0.3 kg), vinyltrichlorosilane (0.3 kg) and N-hydroxymethyl acrylamide (0.3 kg) were added in sequence, the temperature was controlled at 60° C., and stirring was maintained for 10 minutes.

[0043] 3. Add initiator

[0044] Potassium persulfate (0.3 kg) was added as an initiator and stirring was continued for 10 minutes.

[0045] 4. Adding fillers

[0046] Heavy calcium carbonate (1 kg), alumina (0.5 kg) and nano-silica (0.2 kg) were gradually added to ensure that the fillers were evenly dispersed. Butyl acrylate (0.4 kg) and hydroquinone (0.1 kg) were added to improve elasticity and oxidation resistance.

[0047] 5. Defoaming and dispersion

[0048] Defoamer (0.2 kg) and dispersant (0.2 kg) were added and stirring was continued to ensure a homogeneous mix without air bubbles.

[0049] 6. Curing treatment

[0050] After continuing to stir in the reactor for 20 minutes, the mixture is poured into a mold and cured naturally, ensuring that the finished product has high elasticity, excellent wear resistance and crack resistance.

[0051] Example 2: Preparation of high elastic grouting material

[0052] Based on Example 1, the dosage of some materials was slightly adjusted, and the rest of the steps remained the same:

[0053] Acrylate mixture: 18 kg;

[0054] Triethanolamine: 0.2 kg;

[0055] Potassium persulfate: 0.25 kg;

[0056] Methyl methacrylate: 0.6 kg;

[0057] Styrene: 0.25 kg;

[0058] Butyl acrylate: 0.3 kg;

[0059] Diethylenetriamine: 0.15 kg.

[0060] Example 3: Preparation of high elastic grouting material

[0061] Based on Example 1, the formula was further fine-tuned, and the other steps were the same as in Example 1:

[0062] Acrylate mixture: 22 kg;

[0063] Triethanolamine: 0.35 kg;

[0064] Heavy calcium carbonate: 1.2 kg;

[0065] Alumina: 0.6 kg;

[0066] Nano silicon dioxide: 0.3 kg.

[0067] Comparative Example 1: Preparation of grouting material

[0068] The amount of the acrylate mixture was reduced to 15 kg. Alumina and nano-silicon dioxide were not used. The amount of heavy calcium carbonate was increased to 2 kg. The rest of the formula and preparation method were the same as in Example 1.

[0069] Comparative Example 2: Preparation of grouting material

[0070] The amount of the acrylate mixture was kept at 20 kg, but hydroquinone and N-hydroxymethyl acrylamide were not used. Low-purity methyl methacrylate (content 80%) was used. The rest of the formula and preparation method were the same as in Example 1.

[0071] Test Example 1

[0072] For Examples 1-3 and Comparative Examples 1-2, the following performance tests were conducted to comprehensively characterize the elasticity, wear resistance, crack resistance, fluidity and weather resistance of the materials.

[0073] Test items:

[0074] 1. Tensile strength (MPa);

[0075] 2. Elongation at break (%);

[0076] 3. Wear resistance (mg, weight loss after test);

[0077] 4. Crack resistance (5-level rating, 1 is the worst and 5 is the best);

[0078] 5. Fluidity (s, slump time);

[0079] 6. Weather resistance (performance retention rate after 1200 hours of aging, %).

[0080] The following is a detailed description of the performance testing methods for the materials of Examples 1-3 and Comparative Examples 1-2, including equipment, testing procedures and evaluation criteria.

[0081] 1. Tensile strength test

[0082] Test standard: According to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".

[0083] Equipment: Electronic tensile testing machine.

[0084] Test steps:

[0085] 1. Make a standard dumbbell-shaped specimen and place it at room temperature for 24 hours.

[0086] 2. Clamp the sample in the fixture of the electronic tensile testing machine and select an appropriate tensile speed (generally 200 mm / min).

[0087] 3. Record the maximum tensile force when stretched to fracture and calculate the tensile strength (MPa).

[0088] Evaluation criteria: The greater the tensile strength, the stronger the material's tensile resistance, and the more suitable it is for situations that require greater tensile forces.

[0089] 2. Elongation at break test

[0090] Test standard: Refer to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".

[0091] Equipment: Electronic tensile testing machine.

[0092] Test steps:

[0093] 1. Use dumbbell-shaped specimens of the same tensile strength.

[0094] 2. During the stretching process until the specimen breaks, record the stretched length.

[0095] 3. Calculate the elongation at break = (length after stretching - original length) / original length × 100%.

[0096] Evaluation criteria: The higher the elongation at break, the better the flexibility of the material, which is suitable for applications with high elasticity requirements.

[0097] 3. Wear resistance test

[0098] Test standard: Refer to ASTMD4060 "Standard coating material wear resistance test".

[0099] Equipment: Taber abrasion tester, abrasion wheel (CS-17 or similar) and specified weight.

[0100] Test steps:

[0101] 1. Pre-treat the sample and measure the initial weight.

[0102] 2. Fix the sample on the wear tester and set the number of wear times (usually 1000 times).

[0103] 3. After the wear is completed, weigh the sample and calculate the mass difference before and after the wear.

[0104] Evaluation criteria: The smaller the weight loss after wear, the better the wear resistance of the material, and the more suitable it is for use in a wear environment.

[0105] 4. Crack resistance test

[0106] Test standard: Refer to GB / T9341-2008 "Determination of tensile properties of thermosetting plastics".

[0107] Equipment: Temperature and humidity control equipment, aging chamber.

[0108] Test steps:

[0109] 1. Place the sample in a specified temperature and humidity environment for cyclic stretching.

[0110] 2. Record the occurrence of cracks under different tensile states.

[0111] 3. Score according to the generation and development of cracks (scoring scale ranges from 1-5, 1 means easy to crack, 5 means strong crack resistance).

[0112] Evaluation criteria: The higher the score, the more resistant the material is to cracking and the more suitable it is for use in high-stress environments.

[0113] 5. Liquidity test

[0114] Test standard: Based on GB / T11998-2008 "Mortar fluidity test method".

[0115] Equipment: slump cone, slump cone, stopwatch.

[0116] Test steps:

[0117] 1. After filling the slump cone with the sample, place it on top of the slump cone.

[0118] 2. Lift the cone and allow the sample to flow naturally.

[0119] 3. Use a stopwatch to record the time required for the sample to completely level.

[0120] Evaluation criteria: The shorter the fluidity time, the better the fluidity of the material, and it is suitable for occasions with high fluidity requirements.

[0121] 6. Weather resistance test

[0122] Test standard: Refer to GB / T14522-2008 "Accelerated aging test method for plastics exposed to laboratory light sources".

[0123] Equipment: UV aging test chamber.

[0124] Test steps:

[0125] 1. Place the sample in a UV aging test chamber and set the temperature and humidity conditions (50°C, relative humidity 50%).

[0126] 2. Set the UV exposure time to 1200 hours.

[0127] 3. After aging, measure the tensile strength, elongation at break and other properties of the sample, and calculate the weather resistance retention rate = performance after aging / performance before aging × 100%.

[0128] Evaluation criteria: The higher the weather resistance retention rate, the better the weather resistance of the material, and the more suitable it is for long-term exposure to sunlight, wind, rain and other environments.

[0129] Through the above specific testing methods, the performance of Examples 1-3 and Comparative Examples 1-2 can be more accurately and scientifically characterized, and the quality of the materials can be comprehensively evaluated.

[0130] The performance test results are shown in Table 1.

[0131] Table 1

[0132]

[0133]

[0134] Data analysis and results:

[0135] According to the performance test results in Table 1, we can compare and analyze the material properties of Examples 1-3 and Comparative Examples 1-2.

[0136] Tensile strength: The tensile strengths of Examples 1-3 are 3.5 MPa, 3.3 MPa and 3.6 MPa, respectively, which are higher than 2.5 MPa and 2.8 MPa of Comparative Examples 1 and 2. This indicates that the materials in the examples have better tensile strength and are suitable for bearing greater tensile forces.

[0137] Elongation at break: The elongations at break of Examples 1-3 are 250%, 240% and 255%, respectively, which are significantly higher than 180% and 190% of Comparative Examples 1 and 2. This indicates that the materials in the examples have higher flexibility and are more suitable for applications with high requirements for elasticity.

[0138] Wear resistance: The wear resistance test results of Examples 1-3 are 0.4 mg, 0.45 mg and 0.38 mg respectively, which are better than 0.7 mg and 0.65 mg of Comparative Examples 1 and 2. This shows that the materials in the examples have better wear resistance and are suitable for use in a wear environment.

[0139] Crack resistance: In the crack resistance test, Examples 1-3 all received the highest score of 5 points, while Comparative Examples 1 and 2 received scores of 3 and 4 points, respectively. This indicates that the materials in the examples have stronger crack resistance and are suitable for use in high stress environments.

[0140] Fluidity: The fluidity test results of Examples 1-3 are 15 seconds, 16 seconds and 15 seconds respectively, which are much lower than 25 seconds and 20 seconds of Comparative Examples 1 and 2. This shows that the material in the examples has better fluidity and is suitable for use in situations requiring high fluidity requirements.

[0141] Weather resistance: The weather resistance retention rates of Examples 1-3 are 90%, 88% and 92% respectively, which are higher than 70% and 75% of Comparative Examples 1 and 2. This shows that the materials in the examples have better weather resistance and are suitable for long-term exposure to harsh natural environments.

[0142] In summary, the materials of Examples 1-3 are superior to the materials of Comparative Examples 1 and 2 in terms of tensile strength, elongation at break, wear resistance, crack resistance, fluidity and weather resistance. Therefore, it can be concluded that the materials of Examples 1-3 have better comprehensive performance and are more suitable for applications requiring high elasticity and wear resistance and for use in harsh environments.

[0143] The high-elastic, high-strength water-based grouting plugging material prepared by the present invention is an ideal substitute for traditional polyurethane grouting liquid and water curing. It can quickly solidify and provide waterproof effect, and can maintain good ductility and no cracks even in an environment of minus 30 degrees. Its compressive strength is 20 to 50 times that of water curing. For various leakage gaps, only one grouting is required, and no repeated grouting is required. It is in place in one step, and no maintenance is required after plugging, and there will be no problem of repeated leakage. The product is environmentally friendly and non-toxic.

[0144] Features:

[0145] 1. The composite salt has extremely low viscosity and excellent permeability, ensuring that the slurry can penetrate into gaps as small as 0.1mm in width;

[0146] 2. The curing time is adjustable, fast curing takes only 20 seconds, slow curing can take more than 10 minutes;

[0147] 3. The gel has high elasticity and the elongation can reach 200%, which effectively solves the problem of structural expansion and contraction;

[0148] 4. It does not shrink when drying, but expands slightly when exposed to water, solving the problem of dry-wet cycle of gel;

[0149] 5. It has good bonding performance with the concrete base surface, and the bonding strength is equivalent to the strength of the gel itself;

[0150] 6. Good chemical resistance to most acids and alkalis, and not affected by biological damage;

[0151] 7. The slurry and gel are non-toxic, do not endanger the health of workers, do not damage surface water, and are environmentally friendly products.

[0152] Applications:

[0153] This product is suitable for tunnel construction, subway station deformation joints, induced joints, cracks, settlement joints, post-cast strips, villa basement building deformation joints, hollow walls, wall crack seepage, as well as concrete expansion joints and crack leakage treatment in industrial and civil construction fields.

[0154] Construction method:

[0155] 1. Drill holes or make grooves at the leaking part;

[0156] 2. Water can be pressed into the drill hole first to determine whether all cracks are connected or whether more holes need to be drilled;

[0157] 3. Use a hand pump or electric high-pressure pump for grouting. The grouting pressure can be 0.2-0.6MPa. The pressure can be appropriately increased according to the sealing quality and structural conditions to ensure that the slurry penetrates into the structure and fine gaps;

[0158] 4. During the grouting process, if leakage occurs on the surface of the structure, the grouting operation should be stopped immediately, and the leakage point should be sealed by appropriate methods before continuing the grouting.

[0159] Implementation standards:

[0160] Technical indicators (implementation of JC / T2037-2010 "Compound Salt Grouting Material" standard)

[0161] Note:

[0162] 1. This product is a water solution, not flammable or explosive, and should be stored in a plastic container;

[0163] 2. During construction, labor protection should be done well, ventilation facilities should be ensured, and parts that have come into contact with the body should be washed with clean water in a timely manner. If accidentally ingested, please seek medical attention immediately.

[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a high elastic grouting material, characterized in that: include: After the acrylate mixture and triethanolamine are stirred until uniformly mixed, methyl methacrylate, styrene, vinyl trichlorosilane and N-hydroxymethyl acrylamide are added in sequence and stirred; Add initiator and continue stirring to promote the polymerization reaction; Gradually add heavy calcium carbonate, alumina and nano-silica, and after ensuring that the fillers are evenly distributed, add butyl acrylate and hydroquinone, add defoamer and dispersant, continue stirring to remove bubbles and ensure that the fillers are evenly distributed, and obtain a mixture; The mixture is poured into a mold and solidified to obtain the high elastic grouting material.

2. The method for preparing a high elastic grouting material according to claim 1, characterized in that: After the acrylate mixture and triethanolamine are stirred until uniformly mixed, methyl methacrylate, styrene, vinyl trichlorosilane and N-hydroxymethyl acrylamide are added in sequence and stirred while controlling the temperature to 60±5°C.

3. The method for preparing a high elastic grouting material according to claim 1, characterized in that: The initiator is potassium sulfate.

4. The method for preparing a high elastic grouting material according to claim 1, characterized in that: The defoamer is a polyether defoamer.

5. The method for preparing a high elastic grouting material according to claim 1, characterized in that: The dispersant is a polycarboxylic acid dispersant.

6. The method for preparing a high elastic grouting material according to claim 1, characterized in that: The weight ratio of the acrylate mixture, triethanolamine, potassium persulfate, methyl methacrylate, styrene, vinyl trichlorosilane, heavy calcium carbonate, aluminum oxide, nano silicon dioxide, N-hydroxymethyl acrylamide, butyl acrylate, hydroquinone, diethylenetriamine, defoamer and dispersant is 15-22: 0.2-0.35: 0.25-0.3: 0.5-0.6: 0.25-0.3: 0.3: 1-2: 0.5-0.6: 0.2-0.3: 0.3: 0.3-0.4: 0.1: 0.15-0.2: 0.2: 0.

2.

7. A high elastic grouting material, characterized in that: The high elastic grouting material is prepared by the method for preparing the high elastic grouting material according to any one of claims 1 to 6.

8. Use of the high elastic grouting material according to claim 7 in the preparation of building materials.

Citation Information

Patent Citations

  • High-permeability nano modified acrylate grouting material and preparation method thereof

    CN116217783A